INTEGRATIVE DIMENSIONS IN THE THEORY OF JURIDICAL ARGUMENTATION: FROM A CLAIM TO CORRECTNESS TO THE ONLY CORRECT DECISION - PAVLIUK, ANATOLII (Ehrlich’s Journal, 2024)
The article under discussion studies the concepts of a claim to correctness and the only correct decision, as well as the relationship between them. The study has been carried out in terms of the syncretic discursive and/or constructive theory of legal argumentation by Robert Alexy and/or Ulfrid Neumann, the latter theory being regarded as an integrative (normative-analytical and/or normative-empirical) one. The purpose of the article is to explicate the relationship between the concepts of a claim (right) to correctness and the only correct decision (as a regulatory idea) in terms of the integrative ad hoc theory of legal argumentation. In order to achieve this goal, it is essential to consider the following issues: 1) what is the integrative theory of legal argumentation and how its dimensions are combined; 2) how law forms a claim to correctness and how the only correct decision becomes a regulatory idea; 3) what is the relationship between the claim to correctness and the only correct decision as a regulatory idea within the integrative theory of legal argumentation. At the same time, the article points out that the integrative theory of legal argumentation is arbitrarily combined through the elements of its analytical, normative and empirical dimensions. It is interesting that the theory of legal argumentation by R. Alexy and / or U. Neumann foregrounds the concept of “claim” instead of or alongside with the concept of “sense”. In addition, R. Alexy and/or U. Neumann understand the concept of a claim to correctness relying on the theory of speech acts, whereas the only correct decision is perceived as a regulatory idea. The article also describes the relationship between the concepts of a claim to correctness and the only correct decision in logical and mathematical terms of necessary and sufficient conditions. The article concludes that the integrative theory of legal argumentation is a neo-methodological theory with an arbitrary combination of the elements of its analytical, normative and empirical dimensions. What is more, it can be modeled within the paradigm of “claim” rather than “sense”. The basis for R. Alexy and/or U. Neumann’s syncretic theory of legal argumentation in terms of the claim to correctness and the only correct decision is the theory of speech acts and the notion of regulatory idea. The claim to correctness is a sufficient condition for the validity of the concept of the only correct decision as a regulatory idea; however, it is doubtful whether such a claim is a necessary condition.